The Changing Business of Aboriginal and Torres Strait Islander Art: Markets, Audiences, Artists, and the Large Art Fairs - Jones, Tod; Booth, J.; Acker, Tim (2016)
This article analyzes the relationship between the growth of large Australian Aboriginal art fairs and shifts in the fine art market and state policies; audience and art insiders' experiences; and the implications of art fair participation for artists and art centers. In contrast to the traditional gallery model, the art fairs draw buyers and artists together in regional centers, along with families, managers, curators, commentators, administrators, and politicians. Using the assemblages concept, we analyze the emergence of a new engagement that prioritizes social, cultural, and interpersonal aspects of art making and where buyers consume “relational goods” linked to their purchasing context.